SUSTAINABLE MANAGEMENT AND RURAL AGROPOLITAN DEVELOPMENT IN SENDANG VILLAGE OF TULUNGNAGUNG, EAST JAVA: A MULTIDIMENSIONAL ANALYSIS OF SUSTAINABILITY - Rita Parmawati (Universitas Gadjah Mada, 2019)
Studies on sustaniable developemnt show that agropolitan area is one of the urban development concepts that distinctivelu offers a design for sustainable developlemt for planning. The concept of agropolitan area offers a way to fill in the gap of capital flow gap between cities and villages. However, detailed analysis of the variety of sustainability is necesary to examine dimensions of sustanibility. Taking the case of an Angropolitan project in the Sendang villange of Tulungangung East Java), this study aims to identify the level of the sustainability of Agropolitan management. In assessing the level of sustainability, this study employs the method of Multidimensional Scaling (MDS). The framework of sustainable livelihoods is divided into five components of capital : human, natural, physical, financial, and social. The sustainability analysis is carried out by using the Multi-Dimensional Scaling (MDS) approach with Rapid Appraisal Techniques for Fisheries (Rap-fish). Based on Rapfish result, we obtain an index value of capitals : human (54.63%), natural (58,34%), financial (31.55%), physical (22.13%), and social (56.41%). Human, natural, and social capital are categorized as quite sustainable. Financial and physycal aspects appear less sustainable than other aspects. In general, the status of sustainability in the management of the Sendang Agropolitan is quite sufficient.